Predator‐induced maternal and paternal effects independently alter sexual selection. (11th January 2020) - Lehto, Whitley R.; Tinghitella, Robin M.
Abstract: Parental experience alters survival‐related phenotypes of offspring in both adaptive and nonadaptive ways, yielding rapid inter‐ and transgenerational fitness effects. Yet, fitness comprises survival and reproduction, and parental effects on mating decisions could alter the strength and direction of sexual selection, affecting long‐term evolutionary trajectories. We used a full factorial design in which threespine stickleback ( Gasterosteus aculeatus ) mothers, fathers, both, or neither were exposed to a model predator at developmentally appropriate times to test for predator‐induced maternal, paternal, and joint parental effects on daughters' mating behavior. We tested the responsiveness, preferences, and mate choices of adult daughters in no‐choice trials with wild‐caught males who had varied sexual signals. Maternal and paternal predator exposure independently yielded daughters who preferred males who were intermediate in conspicuousness (with duller nuptial coloration and who courted less vigorously), relaxing the typical preference for the most conspicuous males. The combined effects of maternal and paternal predator exposure were not cumulative; when both parents were predator exposed, single‐parent effects on mate preferences were reversed. Thus, we cannot assume that maternal and paternal effects additively combine to produce "parental" effects. Further, joint parental predator exposure yielded daughters who were three times less likely to mate at all. Stress‐induced intergenerational parental effects on reproductive decisions such as those observed here may potentiate rapid transgenerational responses to novel and changing mating environments.